The carbon reduction effect of ESG performance: empirical evidence from Chinese shipping enterprises - Li, Jinpei; Suo, Jiaxin; Huang, Yixuan; Sun, Xiangdong (Frontiers in Marine Science, 2025)
Environmental, social and governance (ESG) practices have become a crucial pathway for the sustainable development of enterprises, and so have shipping enterprises. Based on the unbalanced panel data of China’s A-share listed shipping enterprises from 2009 to 2022, this study uses a multiple regression model to empirically test the impact of ESG performance on carbon emission reduction and its regional heterogeneity. The findings indicate that ESG performance significantly reduces the carbon emission intensity of shipping enterprises, a conclusion that remains robust across various robustness tests and endogenetic analyses. Further heterogeneity analysis reveals that the carbon emission reduction effect of ESG performance is more pronounced in the southern region. These results underscore the importance of strengthening ESG capabilities as a key strategy for promoting the low-carbon transition of shipping enterprises and achieving sustainable development.